Categorising Remaking Methods for Fashion Practitioners - English, Julia (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Within fashion and textiles, practices which transform existing textile waste materials are discussed using various terms, for example upcycling, remanufacturing, or redesign, however, this study will collectively refer to these as remaking practices. Through the examination of 38 cases of remake collaborations occurring within the Australian community between November 2019 to July 2023, this study explores how the fashion remake outcomes can be classified to more effectively support the development of different remaking practices. As a result, the paper proposes a remaking lexicon to encompass eight different methods which can be employed individually or in combination: over-dye, over-print, embellish, alter, splice, piece, patchwork and refabricate. This proposed categorisation draws parallels to traditional fashion production processes, yet also recognises that end-to-end production skills are not required for remaking, instead showcasing that the methods may use different skillsets. In identifying different types of skills, rather than different levels of skills, this paper highlights an opportunity for remaking practices to engage a wider range of actors and encourage a broader range of specialisations than has been previously suggested. The eight methods provide a clear categorisation to enable more critical comparison and evaluation of remaking practices, encouraging discussion into how the fashion industry might build a diverse ecosystem of remake practitioners.